Axial resolution enhancement of light‐sheet microscopy by double scanning of Bessel beam and its complementary beam. Issue 1 (20th August 2018) - Jia, Hao; Yu, Xianghua; Yang, Yanlong; Zhou, Xing; Yan, Shaohui; Liu, Chao; Lei, Ming; Yao, Baoli
Abstract : The side lobes of Bessel beam will create significant out‐of‐focus background when scanned in light‐sheet fluorescence microscopy (LSFM), limiting the axial resolution of the imaging system. Here, we propose to overcome this issue by scanning the sample twice with zeroth‐order Bessel beam and another type of propagation‐invariant beam, complementary to the zeroth‐order Bessel beam, which greatly reduces the out‐of‐focus background created in the first scan. The axial resolution can be improved from 1.68 μm of the Bessel light‐sheet to 1.07 μm by subtraction of the two scanned images across a whole field‐of‐view of up to 300 μm × 200 μm × 200 μm. The optimization procedure to create the complementary beam is described in detail and it is experimentally generated with a spatial light modulator. The imaging performance is validated experimentally with fluorescent beads as well as eGFP‐labeled mouse brain neurons. Abstract : This paper aims to improve the axial resolution of scanning Bessel beam light‐sheet microscopy without sacrificing large field‐of‐view in virtue of propagation‐invariant property of Bessel beam. Compared with two‐photon excitation, the method proposed in this paper provides a cost‐effective access to time lapse 3D imaging with low phototoxicity but high optical sectioning performance.